2021
DOI: 10.1183/13993003.03927-2020
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity within and between physician-diagnosed asthma and/or COPD: NOVELTY cohort

Abstract: BackgroundStudies of asthma and chronic obstructive pulmonary disease (COPD) typically focus on these diagnoses separately, limiting understanding of disease mechanisms and treatment options. NOVELTY is a global, 3-year, prospective observational study of patients with asthma and/or COPD from real-world clinical practice. We investigated heterogeneity and overlap by diagnosis and severity in this cohort.MethodsPatients with physician-assigned asthma, COPD or both (asthma+COPD) were enrolled, stratified by diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 30 publications
4
86
0
2
Order By: Relevance
“…The distribution of blood eosinophils in COPD populations is not different from that seen in healthy patients without the disease [ 98 ], suggesting that the coexistence of a higher count and COPD occurs by chance rather than due to a specific causal mechanism. As noted already, the blood eosinophil count in the large observational NOVELTY study was not different between patients with an ACO diagnosis and those thought to have usual COPD [ 51 ], a finding that held true across the clinician-determined range of disease severity ( Figure 3 ). The diagnostic classification did have some significance as ACO patients were more likely to receive ICS treatment in disease perceived to be mild or moderately severe than was the case if COPD alone was diagnosed.…”
Section: Therapeutic Implications Of Acomentioning
confidence: 68%
See 3 more Smart Citations
“…The distribution of blood eosinophils in COPD populations is not different from that seen in healthy patients without the disease [ 98 ], suggesting that the coexistence of a higher count and COPD occurs by chance rather than due to a specific causal mechanism. As noted already, the blood eosinophil count in the large observational NOVELTY study was not different between patients with an ACO diagnosis and those thought to have usual COPD [ 51 ], a finding that held true across the clinician-determined range of disease severity ( Figure 3 ). The diagnostic classification did have some significance as ACO patients were more likely to receive ICS treatment in disease perceived to be mild or moderately severe than was the case if COPD alone was diagnosed.…”
Section: Therapeutic Implications Of Acomentioning
confidence: 68%
“…Further work on well characterised cohorts preferably with appropriate CT imaging should help clarify these relationships. However, the largest comparative cohort study to date, NOVELTY, found no difference in blood eosinophil counts between the asthma, COPD and asthma-COPD overlap groups that they recruited [ 51 ], suggesting that blood eosinophils are not useful discriminants in routine clinical practice in identifying what physicians felt constituted ACO.…”
Section: A Pathology Of Aco?mentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with chronic obstructive pulmonary disease (COPD), comorbid with asthma (asthma-COPD overlap, ACO) or bronchiectasis (bronchiectasis-COPD overlap, BCO) as well as their coexistence (ABCO), are commonly seen phenotypes, which have been broadly discussed whether they were distinct disease entities, but there is no concluded consensus yet (1). The concept of "ACO" or "asthma + COPD" appeals as a great interest to investigators (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and similar discussion applies to the research of bronchiectasis and COPD overlap (12)(13)(14)(15)(16). Few data was reported on the ABCO phenotype.…”
Section: Introductionmentioning
confidence: 99%